Projektna naloga kot strategija vzgojno-izobraževalnega dela - Papotnik, Amand (Strojniški vestnik, 2002)
This paper deals with the project task as a strategy for education-training activities. The project task is organised as follows: it begins with the conception, and then continues through prototype, technical and technological dokumentation, execution of series production and on to analysis of the work and evaluation of the product-project. In such a task the pupils of several classes or different classes can cooperate so that the work is divided among the classes. The project task is a strategy of education-training activities including the development of divergent thinking, creative capacities, acquiring, developing, exercising and applying knowledge in the areas of technology, production planning, economics, ergonomics, ecology, information processing and computer science, industrial design, etc.
Keywords: delo vzgojnoizobraževalno; strategije dela; naloge projektne; reševanje problemov; tehnični pouk; projektna naloga; metodika